Genome-Wide Signature of Positive Selection in Ethiopian Indigenous and European Beef Cattle Breeds - Mengistie, D.; Edea, Zewdu; Sisay, T.; Dejene, G.; Dessie, Tadelle; Jema, J.; Asefa, E.; Kwan Suk Kim; Samuel, B.; Dadi, H. (Research Square Platform LLC, 2022)
Despite the availability of genomic methods for determining the origin and divergence of domestic cattle in East Africa, particularly Ethiopia, knowledge regarding their genetic adaptability and divergence remain limited. To investigate signatures of selection Ethiopian cattle populations were genotyped with an 80K SNP array and European beef cattle breeds were also used for comparison purposes.